THE DEVELOPMENT OF INSTRUMENT FOR ASSESSING THE QUALITY OF SERVICES IN A PSYCHIATRIC HOSPITAL - Rasulov, A.R. (World of Medicine and Biology, 2016)
The study focuses on evaluation of mental health services in psychiatric hospitals. The new monitoring instrument has been developed to collect reliable information about quality of care provided for in-patients. The assessment was made in eight wards (six male and two female) at the Psychiatric Hospital #1 of the Ministry of Health. The monitoring allowed us to collect important information about hospital conditions, available staff, diagnostics and treatment, patients’ rights protection as well as records management. The instrument made possible to obtain a comprehensive picture about quality of care and existing problems in each of selected wards. The instrument may be recommended for implementation in the other in-patient psychiatric facilities.
Keywords: Mental health service; monitoring; tools; quality management